(untitled) (Journal of Comparative & International Higher Education, 2023)
Universities in Canada are increasingly attracting international students, but few studies have examined their experiences. This research identified the key supports and barriers for international students in order to make policy-relevant recommendations. This convergent mixed-methods study combined survey (n = 104) and interview (n = 14) data to investigate international student experiences through the lens of international students. Exploratory factor analyses revealed writing and mathematics skills and relationships with faculty and students as key factors for success. Frequency analyses revealed that racism was a persistent barrier. Assistance, access, diversity and equity issues were also raised. Open and axial coding of qualitative data corroborated these findings and revealed three dimensions of internationalization according to international students’ perspectives: Exchange; Understanding, Sharing, and Support; and Transformation. Recommendations to universities included offering bursaries to international students from underrepresented regions, developing intercultural awareness of faculty, and providing program-specific student support centres with peer mentors.